2016
DOI: 10.4103/0972-2327.165456
|View full text |Cite
|
Sign up to set email alerts
|

Posterior reversible encephalopathy syndrome with spinal cord involvement (PRES-SCI): A case report

Abstract: Posterior reversible encephalopathy syndrome with spinal cord involvement (PRES-SCI) is a recently described entity with a handful of cases reported in literature. We describe a case of PRES in setting of Henoch-Schönlein purpura (HSP) with involvement of brain stem and spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In contrast to the general prevalence of IgAV (male 2:1 female), neurological involvement in pediatric patients was nearly equally contributed, with 13 girls and 13 boys affected, respectively. Two cases of adult males ( 19 , 35 ) (22 and 42 years of age) and one female patient were found ( 36 ). Bérubé et al, however, reported a 1.5:1 preponderance of male patients ( 38 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast to the general prevalence of IgAV (male 2:1 female), neurological involvement in pediatric patients was nearly equally contributed, with 13 girls and 13 boys affected, respectively. Two cases of adult males ( 19 , 35 ) (22 and 42 years of age) and one female patient were found ( 36 ). Bérubé et al, however, reported a 1.5:1 preponderance of male patients ( 38 ).…”
Section: Resultsmentioning
confidence: 98%
“…In total, we identified 28 cases with IgAV and reversible encephalopathy ( 6 10 , 17 36 ). Twenty six cases were associated with seizures ( 6 10 , 17 19 , 21 31 , 33 , 34 , 36 ), and thereof 14 cases fulfilled all clinico-radiological criteria of PRES ( 6 , 7 , 9 , 10 , 17 25 ). Lava et al indicated the existence of seven other cases, which, however, were not available in English or did not fulfill the radiologic diagnostic criteria of PRES and were therefore not considered a confirmed PRES diagnosis in this summary ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the parieto-occipital lobes are most commonly involved in PRES (98%), frequencies ranging from 10%-68% have been reported for particular regions of the brain [ 2 ]. Different studies have also proposed the introduction of the term posterior reversible encephalopathy syndrome with spinal cord involvement (PRES-SCI) in a case series [ 4 ], with additional cases published elsewhere [ 5 ].…”
Section: Introductionmentioning
confidence: 99%